Reasserting martial masculinity through postmodern militarism: military fantasies, subculture and gender in portrayals of the Japan Self-Defense Forces - Fahrenwaldt, Miklas (The University of Edinburgh, 2025)
The Japan Self Defense Forces (JSDF) are a deeply paradoxical entity. They are a military but must not be called one. They have advanced weaponry but must not use it. Previous studies have explored this paradoxical existence through lenses that focus on political or social constraints such as the difficulty of justifying the JSDF’s existence to a sceptical public, with Sabine Frühstück (2007) famously labeling them “Uneasy Warriors”. Yet, analysing JSDF YouTube videos, the military anime GATE, the JSDF magazine “Mamor” and three JSDF museums, I find hardly any uneasiness at all. Instead, weapons and fighting are unabashedly portrayed as cool and attractive, and a rather traditional warrior masculinity is promoted in all the different sources. Through (visual) discourse analysis, my project interrogates this surprising assertiveness, finding that throughout very different texts, the JSDF consistently presents a commodified, pleasurable version of militarism that reframes military violence as an exciting and thrilling game, escaping the confinement of the JSDF’s paradoxical nature by constructing subcultural fantasies of a heroic and beloved Japanese military. To understand this dynamic, the project draws on Japanese postmodern theorists Asada Akira and Azuma Hiroki to show how popular culture and gender are leveraged to construct, maintain and speak to a military-friendly subculture, where traditional military values are promoted but stripped of their overt political content. Coining the term “apolitical militarism”, my project explains this development as a JSDF embrace of postmodernism, leaning into increased societal siloisation, fragmentation and individualisation to replace the nationalist grand narratives of modern militarism with a shared subcultural database of military tropes. Individuals in the subculture can then draw from this database in highly personalised ways to construct their own, personalised narrative of militarism, thus outsourcing overtly political meaning-making from the content creator to the content consumer. In this way, the project builds on and further develops existing analyses of JSDF militarism and gender to show how the JSDF of the 21st century has created an illusion of consensus that allows it to simply sidestep its underlying paradox without resolving it. But while the strain resulting from the JSDF’s fundamental paradox might be extraordinary, the existence of such underlying tensions between adhering to a society’s democratic values and exercising military violence is not unique to Japan and in fact a challenge faced by other postmodern militaries as well. Rather than an “exception” or “abnormality”, as it is sometimes described in International Relations discourse, the JSDF then is “avant-garde” (Frühstück, 2004), a pioneer and prototype for new kind of “apolitical militarism” that is located first and foremost in the cultural sphere rather than national politics.
Keywords: Japan Self Defense Forces; JSDF; gendered imagery; JSDF-portrayal; apolitical militarism; culture and consumption; postmodernism; societal fragmentation; Japanese military subculture